Purple Urine Bag Syndrome in Two Elderly Men with Urinary Tract Infection. (17th August 2015) - Van Keer, Jan; Detroyer, Daan; Bammens, Bert
Abstract : Purple urine bag syndrome is a rare condition in which purple discoloration of urine inside its collection bag occurs. We describe two illustrative cases. The first patient is an 81-year-old man who was hospitalized for a newly diagnosed lymphoma with acute obstructive renal failure for which a nephrostomy procedure was performed. During the hospitalization, a sudden purple discoloration of the suprapubic catheter urine was noted, while the nephrostomy urine had a normal color. Urine culture from the suprapubic catheter was positive for Pseudomonas aeruginosa and Enterococcus faecalis ; urine from the nephrostomy was sterile. The second case is an 80-year-old man who was admitted for heart failure with cardiorenal dilemma and who was started on intermittent hemodialysis. There was a sudden purple discoloration of the urine in the collection bag from his indwelling catheter. He was diagnosed with an E. coli urinary infection and treated with amoxicillin and removal of the indwelling catheter. These two cases illustrate the typical characteristics of purple urine bag syndrome.